The Effect of Work Demand, Role Conflict, and Role Ambiguity on Work-Family Conflict (Impact of Work From Home due to The Covid-19 Pandemic): The Effect of Work Demand, Role Conflict, and Role Ambiguity on Work-Family Conflict (Impact of Work From Home due to The Covid-19 Pandemic) - Farika Nikmah; Titien Indrianti; Joni Dwi Pribadi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
Because of the Covid-19 pandemic, this research's background was to break the chain of virus spread, and the government requires physical distancing. Working from home, which causes many employees to work from home, creates conflicts for married female workers. The research objective is to examine and analyze the direct effect of job demands, role conflict, role ambiguity on work-family conflicts. Data were obtained through questionnaires and submitted online to 100 married women who work in universities in East Java, Indonesia, both public and private, and then the analysis was carried out using Partial Least Square (PLS). The results showed that all hypotheses were accepted, and the most dominant influence was role conflict on family-work conflicts. The conclusion is that married women experience many conflicts in carrying out their jobs because other demands must also be considered, namely the mother and wife's role.